KINERJA PELAYANAN JALAN PADA DISTRIBUSI ANGKUTAN BARANG DI KOTA PADANG - Hendrialdi Hendrialdi (UNIMAR AMNI Semarang, 2019)
The distribution of freight transport in Padang City is carried out by using light truck, truck and heavy truck. They operate at peak hours in morning and daylight. The purposes of this research are to find out the distribution pattern of freight transport, road pattern performance, and the effect of freight transport on road performance. This research is assisted by Teacher Friendly Transportation Program (TFTP) to figure out the traffic flow, to evaluate traffic characteristics, and to analyze the alternative solution. This research is conducted by interviewing private companies which registered in Transportation Department to find out the distribution pattern of freight transport, and also by traffic volume survey on some roads to find out the characteristics and the composition of the traffic in Padang City. The analysis results showed performance was 298 km of the length of road networking. The average capacity was 1258 vehicles-km with 1304 vehicles-km of networking performance and the total density in system was 2%. The combination of the both of the result has been performed 148.889 vehicles-km of the networking performance and 41% of traffic density. The solution to reduce the traffic load of networking performance has been conducted by creating the bypass of freight transportation that the output of traffic load in TFTP has been resulted 1013 vehicles-km of networking performance. The combination of traffic load output of freight transportation and the existing traffic load output without freight transportation produced 148.602 vehicles-km of networking performance output.Keywords : Freight transportation, Distribution pattern, Road performance Distribusi angkutan barang di Kota Padang dilakukan dengan truk ringan, truk, dan truk berat yang beroperasi pada jam-jam sibuk di pagi dan siang hari. Tujuan dari penelitian ini adalah untuk mengetahui pola distribusi angkutan barang, kinerja jaringan jalan, dan pengaruh angkutan barang terhadap kinerja jalan. Penelitian ini dibantu oleh Program Transportasi Ramah Guru (TFTP) untuk mengetahui arus lalu lintas, untuk mengevaluasi karakteristik lalu lintas, dan untuk menganalisis solusi alternatif. Penelitian ini dilakukan dengan mewawancarai perusahaan swasta yang terdaftar di Departemen Perhubungan untuk mengetahui pola distribusi angkutan barang, dan juga dengan survei volume lalu lintas beberapa jalan untuk mengetahui karakteristik dan komposisi lalu lintas di Kota Padang. Hasil analisis menunjukkan kondisi saat ini kinerja jalan masih 298 km dari panjang jaringan jalan. Kapasitas rata-rata adalah 1258 kendaraan-km dengan 1304 kendaraan-km kinerja jaringan dan kepadatan total dalam sistem adalah 2%. Kombinasi dari kedua hasilnya telah dilakukan 148.889 kendaraan-km dari kinerja jaringan dan 41% dari kepadatan lalu lintas. Solusi untuk mengurangi beban lalu lintas dari kinerja jaringan telah dilakukan dengan menciptakan bypass transportasi barang sehingga output dari beban lalu lintas di TFTP telah menghasilkan 1013 kendaraan-km dari kinerja jaringan. Kombinasi output beban lalu lintas transportasi barang dan output beban lalu lintas yang ada tanpa transportasi barang menghasilkan 148,602 kendaraan-km dari hasil kinerja jaringan.Kata kunci : Transportasi barang, Pola distribusi, Kinerja jalan